Mining Disease-Resistance Genes in Roses: Functional and Molecular Characterization of the Rdr1 Locus - Terefe-Ayana, Diro; Yasmin, Aneela; Le, Than L.; Kaufmann, Helgard; Biber, Anja; Kuehr, Astrid; Linde, Marcus; Debener, Thomas (Frontiers in Plant Science, 2011)
The interaction of roses with the leaf spot pathogen Diplocarpon rosae (the cause of black spot on roses) is an interesting pathosystem because it involves a long-lived woody perennial, with life history traits very different from most model plants, and a hemibiotrophic pathogen with moderate levels of gene flow. Here we present data on the molecular structure of the first monogenic dominant resistance gene from roses, Rdr1, directed against one isolate of Diplocarpon rosae. Complete sequencing of the locus carrying the Rdr1 gene resulted in a sequence of 265,477 bp with a cluster of nine highly related TIR-NBS-LRR (TNL) candidate genes. After sequencing revealed candidate genes for Rdr1, we implemented a gene expression analysis and selected five genes out of the nine TNLs. We then silenced the whole TNL gene family using RNAi (Rdr1-RNAi) constructed from the most conserved sequence region and demonstrated a loss of resistance in the normally resistant genotype. To identify the functional TNL gene, we further screened the five TNL candidate genes with a transient leaf infiltration assay. The transient expression assay indicated a single TNL gene (muRdr1H), partially restoring resistance in the susceptible genotype. Rdr1 was found to localise within the muRdr1 gene family; the genes within this locus contain characteristic motifs of active TNL genes and belong to a young cluster of R genes. The transient leaf assay can be used to further analyse the rose black spot interaction and its evolution, extending the analyses to additional R genes and to additional pathogenic types of the pathogen.